Code, and Other Laws of Blockchain. - Zou, Mimi (Oxford Journal of Legal Studies)
There has been burgeoning interest among legal scholars in recent years regarding the implications of blockchain technology for the law. Two thoughtful monographs that go beyond the hyped claims of enthusiasts and cynics are Primavera De Filippi and Aaron Wright's Blockchain and the Law: The Rule of Code and Kevin Werbach's Blockchain and the New Architecture of Trust. While the two books have different focal points, both contain a common Laurence-Lessig-inspired theme of 'code as law' in which decentralised blockchain networks are viewed as a regulatory 'modality' or 'architecture' with its own system of rules. However, as this article argues, blockchain is not outside the law or the existing legal system. Code necessarily interacts with other modes of regulation, namely the market, social norms and law, in constraining the operation of blockchain applications such as smart contracts. This argument also situates smart contracts in a relational analysis of real-world contracting practices.